Hailey-Hailey Disease: Case Series and Review of Systemic Medications - Kamran Balighi; Zahra Razavi; Maryam Daneshpazhooh; Vahide Lajevardi; Kambiz Kamyab-Hesari; kimia ghafouri (Mattioli1885, 2024)
Introduction: Hailey-Hailey disease (HHD) is a rare inherited blistering skin disorder characterized by a chronic relapsing course. While it doesn't pose a serious threat to the patient's health, the quality of life can change. Unfortunately, there is currently no standard treatment for this condition. Objective: In this observational retrospective cohort study, our aim was to discover the demographic characteristics and treatment strategies for managing Hailey-Hailey disease. Methods: In this retrospective cohort study, we documented the demographic, clinical, and histopathological characteristics beside various treatment employed options of patients diagnosed with HHD at Razi Hospital over the past 14 years. Results: A total of 32 patients with HHD were enrolled in the study (15 male and 17 female). The mean age of patients was 50.41 ± 13.15 (22-77) years. The average age of disease onset was 37.31 ± 11.88 (15-60) years. Among the participants, 16 individuals (50%) affirm a positive family history of some kind of pemphigoid blisters. The most common site of disease activity was the inguinal area, observed in 14 patients (33.33%). Histopathological examination discovered the existence of suprabasal acantholysis in all of the specimens. Worthily, direct immunofluorescence analysis showed negative results in all skin biopsies. All patients received topical steroids and either topical or systemic antimicrobial agents. In cases of flares, systemic steroids were the most popular and favorable treatment choice during flares. Conclusion: Indeed, Hailey-Hailey disease, characterized by its chronic inflammatory and rare nature with a relapsing and remitting course, poses a significant challenge for dermatologists. The treatment of HHD has been less than satisfactory and it often presents a challenge and could be misdiagnosed. Among the available treatment options, topical steroids and antimicrobial agents are the most commonly administered therapies.